Literature Review: Optimizing Religious Potential in Social Innovation and Community Development - Adam Hafidz Al Fajar; Elfira Zidna Almaghfiro; Syamraeni Syamraeni (Journal of Noesantara Islamic Studies, 2024)
This study explores the crucial role of religion in social innovation and community development, focusing on how religious values can be optimized to create positive and sustainable social change. Using a qualitative approach and a literature review method, this research analyzes various studies that demonstrate the unique capabilities of faith-based organizations in providing social services, supporting vulnerable groups, and creating innovative solutions to address social challenges. The findings indicate that religious communities tend to have high social solidarity, which enables them to effectively organize relief efforts, especially in crisis situations. While the potential of religion in social innovation is significant, there are still conceptual and practical challenges in integrating religious values into development policies and programs. The study recommends the need for interfaith dialogue and cross-religious cooperation to reduce social tensions and create a more inclusive and equitable society. Overall, this research affirms that religion can serve as a catalyst for positive and sustainable social change.